PENGARUH PROFIT SHARING RATIO, ZAKAT PERFORMANCE RATIO DAN DEWAN PENGAWAS SYARIAH TERHADAP KINERJA KEUANGAN BANK UMUM SYARIAH TAHUN 2019-2024 - Wanda Afriliani; Iwan Fakhruddin; Eko Hariyanto; Rina Mudjiyanti (LPPM STIE Muhammadiah Bandung, 2026)
This study aims to analyze the effect of the profit sharing ratio (PSR), zakat performance ratio (ZPR), and the sharia supervisory board (SSB) on the financial performance of Islamic Commercial Banks (BUS) in Indonesia for the period 2019–2024. Financial performance is measured using return on assets (ROA). This study uses a quantitative approach with secondary data obtained from the annual reports of Islamic banks published by the Financial Services Authority (OJK). The sampling technique used purposive sampling with pooled unbalanced panel data, resulting in 74 observations from 14 Islamic banks. The analysis method used is panel data regression with a Random Effect model, which was selected based on the results of the Hausman test. The results show that the profit sharing ratio (PSR) has a negative effect on ROA, the zakat performance ratio (ZPR) has a positive effect on ROA, and the sharia supervisory board (SSB) has no effect on ROA.